EFEKTIVITAS BERITA LOKAL KOMPAS TV TERHADAP KEBUTUHAN INFORMASI SEPUTAR COVID-19 - Baihaki, Ahmad; Kurnia, Kurnia (MediaKom : Jurnal Ilmiah Komunikasi, 2023)
During the Covid-19 pandemic the news media played a central role in providing important information from governments, health authorities and expert sources to a wider audience to combat the Corona Virus and the information landscape in health literacy. Television is one of the mass media that has an important role as the main news provider for the wider community because news in the mass media actually has a quite crucial role in educating, creating awareness and informing all forms of valid information to the public. The focus of the current study aims to determine the effectiveness of local news Kompas TV on the need for information sources about Covid-19. This fact seeks to provide references in the academic and practical fields in understanding how much effectiveness local news Kompas TV has in meeting information needs regarding Covid-19. An explanatory quantitative approach with a positivism paradigm and data collection techniques through Google Form with a 7-point Likert scale measurement level are used in the current study. The purposive sampling technique was applied as a way of determining research respondents for the 2018 STIKOM InterStudi students with criteria as active viewers of local news regarding the development of the Covid-19 pandemic condition on the Kompas TV television station at least four times a week. Test instrument validity and reliability are used in the current research to determine the characteristics and level of consistency of data collection tools. The data analysis phase uses a simple regression analysis technique to determine the results of the proposed presumption hypothesis. The results of the study show that the effectiveness of local news Kompas TV has a significant effect on the need for public information sources about Covid-19 for students and active students of STIKOM InterStudi class 2018.